Flood risk and disaster management in Freetown, Sierra Leone : option for community flood disaster management - Sellu, Gajikoh Mohamed
Flood disaster has been a major issue affecting many coastal communities globally including Freetown, the seaside capital city of Sierra Leone. The need for housing due to significant in-migration resulted to pressure in the urban space dominated by hills overlooking the city which deforestation, stone mining and construction of hillside settlements are increasing the rate of runoffs during rainy seasons. The study identified the absence of Flood Preparedness Framework and lack of community participation as the reasons why resilience efforts to mitigate against floods have not reduced the economic, physical and environmental damages caused by floods in the past. Based on field work, observation and interviews carried out for this study on the strategy on how to improve flood resilience measures in Freetown, the study carried out the following investigation; 1) assessment of the levels of flood vulnerability and extent of flood damages experienced by these communities; 2) investigation on the levels of community participation performance in their preparedness efforts to reduce the impact of floods and 3) assessment of the flood resilience measures of the flood affected communities. Early preparedness measures through active community participation will help improve flood resilience measures in Freetown. This study also recommends a long-term policy to tackle floods through the provision of affordable housing for the urban poor to relocate them into safer zones free from the risk of flooding. This will protect urban sprawl, protect “Environmentally Sensitive Areas” (ESAs) and reduce the risks of flooding in Freetown.